PROFIL KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN MENURUT DAVID KEIRSEY (KadikmA, 2018)
This research aims to describe the profile of the students’ ability in solving mathematics problem in terms of personality according to David Keirsey which includes guardians, artisan, idealists, and rationales. The research subject is four students who are obtained from one student of each personality type in SMKN 2 Jember. MBTI questionnaire, problem-solving test, and interview are used as the data collection method. The analysis of problem-solving test and interview shows that in the stage of understanding and planning the settlement all students are able to fulfill this stage. In the stage of carrying out the plan, SG, SA, and SI students bring about the plan that is made before, while SR student tend to do it based on their remembering skill and it is not appropriated with the existing formula. In the stage of re-checking, only SA and SI students always recheck the steps of processing along with the obtained result. However, SG and SR students do not recheck their work. Besides, SA and SI students have more than one alternative solutions. Keywords: Polya Phases, Personlaity, MBTI